2014
DOI: 10.1021/jm401832j
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Human Transthyretin Complexed with Glabridin

Abstract: Transthyretin (TTR) is a plasma protein implicated in human amyloid diseases. Several small molecules that bind to the thyroxine-binding site of TTR have been shown to stabilize the TTR tetramer and to inhibit amyloid fibril formation of TTR. Herein, we demonstrated that glabridin (Glab), a prenylated isoflavan isolated from Glycyrrhiza glabra L., inhibited aggregation of TTR in a thioflavin assay. The TTR-Glab complex structure revealed a novel binding mode including a CH-π interaction with A108 and a hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 52 publications
2
48
0
Order By: Relevance
“…The ΔG value calculated for the PON2–glabridin interaction in this study indicates that hydrophobic forces play a major role in this binding . According to recent investigations, in interactions of glabridin with proteins, the A and C hydrophobic rings of glabridin bind to the hydrophobic site of the protein, while ring B of glabridin is located in the hydrophilic site of the protein . Glabridin possesses a highly hydrophobic subunit fused with ring A, which may explain its strong binding affinity to PON2.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The ΔG value calculated for the PON2–glabridin interaction in this study indicates that hydrophobic forces play a major role in this binding . According to recent investigations, in interactions of glabridin with proteins, the A and C hydrophobic rings of glabridin bind to the hydrophobic site of the protein, while ring B of glabridin is located in the hydrophilic site of the protein . Glabridin possesses a highly hydrophobic subunit fused with ring A, which may explain its strong binding affinity to PON2.…”
Section: Discussionsupporting
confidence: 51%
“…Glabridin reached a maximum concentration (87 nmol/L) 1 h after administration, which decreased gradually over 24 h. These findings imply that like other flavonoids, glabridin's beneficial effect might be exerted by a mechanism that is not necessarily related to its antioxidant property. Accumulating evidence indicates that glabridin, like other flavonoids, interacts directly with proteins and modulates their activities .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DSSP analysis indicated that the H88 mutants adopted secondary structures similar to that of the WT (Table S2) . The quaternary structures of the H88 mutants were superimposed on that of the WT (PDB ID: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=4N85) , resulting in RMSD values higher than that for the V30M mutant (PDB ID: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=4PWE) (Table ) , which is the most prevalent cause of FAP. These results implied that the quaternary structures were more influenced by the mutations at the 88 position than by those at the 30 position.…”
Section: Resultsmentioning
confidence: 99%
“…The TTR amyloid fibril formation assay was performed according to the previous study. 24) Briefly, V30M-TTR was incubated in the presence of the compounds at pH 4.5 for 4 d, and then the amyloid fibrils were quantified using thioflavin-T by fluorometry (excitation: 440 nm; emission: 484 nm).…”
Section: Drugs For Attrmentioning
confidence: 99%